Quasi-static thermal modelling of multi-scale sliding contact for unlubricated brush seal materials - Xia, Q; Gillespie, D; Owen, A; Franceschini, G (American Society of Mechanical Engineers, 2018)
Prediction of the contact temperature between two materials in high speed rubbing contact is essential when analysing the wear mechanism and modelling wear rate for unlubricated contact. Conventionally the assumptions used for a pin-on-disc configuration are either a steady heat source at the contact for slow speed rotation or an annular source along the rubbing track at high rotating speeds. In this paper, the rotating heating source is solved using an in-house finite element method (FEM) code. This captures the full geometry and rotating speed of the rubbing bodies. The transient heat transfer problem is modelled in a quasi-static way: eliminating the computational cost of a transient 3D simulation. This reduced-order model is analytically shown to be suitable for contact temperature prediction over a wide range of rotating speeds, anisotropic thermal conductivity, and non-uniform thermal boundary conditions. The model calculates heat partition accurately for a thin rotating disc and short pin combination, which cannot be predicted using existing analytical solutions. The quasi-static numerical model and in-house FEM solver are validated against Ansys Mechanical and experimental measurements using infrared thermography. The numerical result demonstrates that the annular source assumption can significantly under-predict the contact temperature, especially at the rubbing interface. Explicit modelling of a thin disc results in a higher heat partition coefficient compared with the commonplace semi-infinite length assumption on both static and rotating components. Furthermore, the thermal anisotropy for bristle tufts is numerically evaluated, and the tuft-on-disc configuration is compared to the pin-on-disc configuration. Despite the effective thermal conductivity in the bristle tuft being approximately one order of magnitude lower than along the bristle length (treating the bristle as a porous medium), its impact on heat partition and contact temperature is shown to be limited.